Photosynthetic performance of the Atlantic brown macroalgae, Cystoseira abies-marina, Dictyota dichotoma and Sargassum vulgare, measured in Gran Canaria on site. - Häder, Donat-Peter; Porst, Markus; Lebert, Michael (Environmental and Experimental Botany, 2001)
Photosynthetic performance was determined in three common Atlantic brown macroalgae, Cystoseira abies-marina, Dictyota dichotoma and Sargassum vulgare, in Gran Canaria, Canary Islands, on site. The photosynthetic quantum yield was measured with both a portable PAM instrument on site and a diving PAM under water in the habitat. In parallel, solar radiation was measured continuously above and under water by means of two three-channel dosimeters, ELDONET (Real Time Computer, Möhrendorf, Germany), in three wavelength ranges, UV-A, UV-B and PAR. The effective photosynthetic quantum yield decreased in all species in response to exposure to 15 min of solar radiation but recovered in the subsequent shade conditions within several hours. A 30-min exposure caused an even more profound photoinhibition from which the algae recovered only partially. Most of the effect was due to visible radiation, however, the UV wavelength range, and especially UV-B, considerably enhanced the decrease in photosynthetic quantum yield. In all species except Sargassum a significant photoinhibition was detected at their growth sites at high solar angles in the water column, measured with the diving PAM. © 2001 Elsevier Science B.V.
UnivIS-Import:2015-03-09:Pub.2001.nat.dbio.LBIPDH.photos
Keywords: Ecophysiology; PAM fluorescence; Phaeophyta; Photoinhibition; Photosynthetic yield; Solar radiation